PENERAPAN PERDA NOMOR 2 TAHUN 2011 TENTANG PAJAK PARKIR PERSPEKTIF PERLINDUNGAN HUKUM PENGGUNA PARKIR (STUDI KASUS DI KOTA MATARAM) - Gazali Gazali (Universitas Islam Negeri Mataram, 2021)
Services as stipulated in Article 1 point 5 of the Consumer Protection Act, services are any services in the form of work or achievements that are made available to the public to be utilized by consumers. Services are business products, both in the form of work and achievements from business actors to provide a service to consumers with the aim of obtaining a profit. So in this case all negative consequences that harm consumers from using these services are the responsibility of the business actor. The responsibility of parking service business actors in providing and providing the best service to consumers is a very important part of the framework of taking responsibility in the event of loss of goods due to the negligence of parking service business actors.